Preliminary results on the role of the coach-athlete relationship in a developing ski nation - Chroni, S.; Lefoussi, I.; Kalomirou, M. (Science and Skiing IV, 2009)
INTRODUCTION: The relationship that develops between a coach and an athlete has an important role. Jowett and colleagues in the recent years have explored this dyadic relationship as a condition where, thoughts, emotions, and behaviors influence both parts and consequently the success of the dyad. It is through this relationship that the athlete matures psychosocially and athletically. However, our knowledge on factors that influence this relationship is still theoretical and empirical. According to Mondello and Janelle (2001) coaches appear to differentiate their behaviors based on the athlete's gender, while coaching behaviors influence athletic performance and results. The purpose of this study was to explore potential differences between female and male Greek alpine ski athletes on the relationship they develop with their male coaches with regard to the constructs of closeness, commitment, and complementarity as these three appear to determine the dynamics and the quality of the dyadic relationship.